Factors in the Adoption of Beef Cattle Artificial Insemination (AI) Technology in Brebes Regency - Lucie Setiana; Dadang Mulyadi Saleh; Aras Prasetiyo Nugroho; Dayu Lingga Lana (Jurnal Penyuluhan, 2020)
Efforts to increase beef cattle population and genetic in Brebes Regency can be done by using artificial insemination (AI) technology approach.Therefore this study aims to determine the factors that influence the ability of beef cattle farmers in adopting artificial insemination technology (AI) in Brebes Regency. Survey method was applied to observe beef cattle and farmers. Sampling technique used Slovin formula with 90% significant rate to observe variables, namely the ability of farmers to adopt AI technology (Y); social factors (X1) consisting of age (X1.1), educational background (X1.2), farming experience (X1.3), herd size (X1.4); technical factors consisting of S/C (X2.1) and oestrous detection (X2.2); and economic factor is AI costs (X3). The research data obtained were analysed using descriptive analysis and correlation. The results showed that adoption of artificial insemination in beef cattle in Brebes Regency had a negative correlation with age (X1.1) (rs = -0.498), did not correlate with educational background (X1.2) (rs = 0.221), farming experience ( rs = X1.3) (rs = -0.056), and the herd size (X1.4) (rs = 0.094) as social factors; does not correlate with the value of S/C (X2.1) (rs = 0.203) and estrous detection (X2.2) (rs = 0.259) as technical factors; and negatively correlate.ed with AI cost (X3) (rs = -0,661) as an economic factor. From the results of the study, it can be concluded that the adoption of artificial insemination in beef cattle in Brebes Regency is influenced by social and economic factors, especially from the age factor and AI cost factor that is less supportive.